2022
DOI: 10.54393/pjhs.v3i01.46
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Urinary Tract Urolithiasis using Computed Tomography

Abstract: Renal stone disease is the most common urinary system disease, existing in third after urinary tract infection and prostate disease in urological departments and accounting for 10-15% of all cases. Objective: To evaluate urolithiasis on Computed Tomography (CT KUB). Methods: It is a cross sectional study carried out at the private Sector Hospital of Gujrat, Pakistan over 4 months from December 2021 to March 2022. A sample size of 50 patients was calculated via a convenient sampling approach using the mean from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…In the current study, males were most commonly affected with kidney stones 28(56%) than females 22(44%) due to low uid intake. A previous study [26] also reported that males were most commonly to have kidney stone than females. In the current study, it was observed that elderly people were most commonly involved in this disease.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In the current study, males were most commonly affected with kidney stones 28(56%) than females 22(44%) due to low uid intake. A previous study [26] also reported that males were most commonly to have kidney stone than females. In the current study, it was observed that elderly people were most commonly involved in this disease.…”
Section: Discussionmentioning
confidence: 75%
“…In most people, low intake of water was the most common reason for kidney stones. A previous study [26] also concluded that low intake of water was the main reason for kidney stones in most patients. This study was found that there is no correlation between lication of stone and stone size just as explain in a previous study [7].…”
Section: Discussionmentioning
confidence: 88%